Transseptal Implantation of a Left Ventricular Pacing Lead for an Ectopic Location of the Coronary Sinus Ostium in the Left Atrium. Issue 2 (31st March 2011) - MONDOLY, PIERRE; MARACHET, MARIE‐AGNÈS; MASSABUAU, PIERRE; RUMEAU, PHILIPPE; MAURY, PHILIPPE; DELAY, MARC; DUPARC, ALEXANDRE
<x xml:space="preserve">Abstract</x> Congenital abnormalities of the coronary sinus (CS) are rare but can be responsible for unsuccessful implantation of a cardiac resynchronization therapy device. We report the case of an ectopic drainage of the CS in the left atrium. A left ventricular lead was implanted by the transseptal route. (PACE 2013; 36:e51–e52)